RESPONSE OF SOME BREAD WHEAT GENOTYPES TRITICUM AESTIVUM L . TO SEED PRIMING BY MANGANESE - BAYDAA A. ALALWANI; SAIEED A. FAIATH (مجلة جامعة الانبار للعلوم الصرفة, 2013)
Afield experiment was carried out in Education college for women AL-Anbar University during the winter season 2009 – 2010 . the objective was to study the response of three wheat genotypes ( Austuraly S.D.30 , Abu grab3 , Sham6 ) for priming by three concentration of Mn (0 , 5,10) ppm – Mn and its effects on Germination , Growth , chlorophyll a and b concentration . Genotype wheat seeds were soaked in water and in different concentration of Mn (0 , 5 , 10) ppm for 12 hours then dried back and storage in dark at small plastic pots in the incubator at 40 for week. Afield experiment was carrid out according to split / plot system with randomized complete block design (R.C.B.D) . A total of 27 treatment with three replication , the area of each experiment unite was (2 x 2.5) m2. seeds was sown in rows in ten rows for unit treatment.A statistical analysis was done for data and treatment means were compared by least significant different (L.S.D) at 0.05 significants level. The Abu Graib3 genotype was showed asignificant effect in speed germination and leaf area 91.66 % and 25.84 cm2 respectivlly .The Sham6 genotype showed asignificant effect in Spike wight and chlorophyll a 3.66 gm 2.05 mg / gm respectivlly The genotypes had no significant effect on Spike length , chlorophyll b and biological yield . The concentration of Mn-seed Priming had asignificant effect on some studies characters .the concentration 10 ppm-Mn was the superior in speed germination , leaf area, chlorophyll a and biological yield83.22 %, 28.51 cm2 , 2.40 ml / gm, 1222 kg / h respectivlly. The priming treatment was showed no significant effect of spike length , spike weight , chlorophyll b . The interaction effect of Abu graib3 genotype and concentration 10 ppm- Mn was superior in spreed germination 93.67 %.The interaction effect austuraly S.D.30 and concentration 10 ppm-Mn was showed asignificant effect in leaf area 29.18 cm2. There was asignificant interaction between Sham6 and concentration 10 ppm-mn on spike weight , chlorophyll a , chlorophyll b and biological yield 3.80gm, 2.50 ml/gm, 1.55 ml/gm, 1300 kg / h.There was no significant interaction between wheat genotype and seed priming concentration on spike length.